Automatic Switching Algorithm for Photovoltaic Power Generation System - Ivan Husain; Canny Dahlia; Feri Yusivar (IAES Indonesia Section, 2018)
within remote area worldwide, solar panel is still considered as an alternative with lower efficiency rate and a complex system needing backup source and storage such as battery. PI MPPT controller then used to remarkably improve the efficiency rate of the solar panel by maintaining it on its Maximum Power Point (MPP) reference. However, tackling the complexity of photovoltaic generator for remote area require another solution. This paper provide a simple yet applicable solution by presenting an algorithm to automatically control the photovoltaic generator system for remote area. The algorithm logic is determined by the key parameters from each systems inside, which are solar panel, PI Boost Converter, Battery, and Load. The simulation result proves that the algorithm is able to provide an appropriate result with all condition working properly. Thus, the algorithm is eligible to be applied and to be developed further